Pregnancy loss and risk of cardiometabolic multimorbidity in Chinese women: the China Kadoorie Biobank study - Sha Huang; Siyu Zou; Jiayi Hee; Ruofan Gongye; Shunqing Xu; Kun Tang (BMC, 2024)
Abstract Background While the association between pregnancy loss and individual cardiometabolic diseases (CMDs) is well-established, its impact on the risk of coexisting CMDs remains unclear. Therefore, the aim of this study is to investigate the association between pregnancy loss with the risk of cardiometabolic multimorbidity in Chinese women. Method We analyzed the cross-sectional data of 299,582 female participants aged 30-79 years old from the China Kadoorie biobank. Cardiometabolic multimorbidity was defined as the coexistence of two or more CMDs, including coronary heart disease, stroke, hypertension, and diabetes. Multivariable logistic regression was used to evaluate the odds ratios (ORs) between the number and type of pregnancy loss with the risk of cardiometabolic multimorbidity, characterized by the number and type of CMD. Results After adjusting for confounding factors, pregnancy loss was found to be significantly associated with increased cardiometabolic multimorbidity risk (OR, 1.13 95% CI 1.08-1.19). Specifically, pregnancy loss due to spontaneous and induced abortion (OR 1.10, 95% CI 1.03-1.18 and OR 1.13, 95% CI 1.08-1.19, respectively). In contrast, no significant association was found between stillbirth and cardiometabolic multimorbidity (OR 1.03, 95% CI 0.95-1.11). The risk of cardiometabolic multimorbidity increases as the number of pregnancy loss increases (one pregnancy loss: OR 1.10, 95% CI 1.05-1.16, two or more pregnancy loss: OR 1.16, 95% CI 1.10-1.22). Similarly, the diagnosis of multiple CMDs increases with increasing number of pregnancy loss. Pregnancy loss was related to higher risk of cardiometabolic multimorbidity across most CMD combinations of CMDs. Conclusion Pregnancy loss, in particular, spontaneous and induced abortion was significantly associated with greater risk of cardiometabolic multimorbidity. The associations were stronger among those with recurrent pregnancy loss.